Mathematical simulation of separating work tool technological process - Tabor, S.; Lezhenkin, Oleksandr; Леженкін, Олександр Миколайович; Леженкин, Александр Николаевич; Halko, Serhii; Галько, Сергій Віталійович; Галько, Сергей Витальевич; Miroshnyk, A.; Kovalyshyn, S.; Vershkov, Oleksandr; Вершков, Олександр Олександрович; Вершков, Александр Александрович; et al. (My University, 2019)
The article describes the technological process of separation of the heaped-off pile of wheat. A mathematical model in the form of regression equations was obtained based on a full-factor experiment. Using the methods of mathematical analysis, the regression equations were investigated for the highest and lowest values. The values of the factors were obtained, for which the response function has the highest values, then the response surfaces were constructed and analyzed.
Keywords: technological process; mathematical simulation